1999
DOI: 10.1002/srin.199905647
|View full text |Cite
|
Sign up to set email alerts
|

Activity of chromium oxide and phase relations for the CaO‐SiO2‐CrOX system at 1873 K under moderately reducing conditions

Abstract: In order to optimize the slag composition operated in the decarburization process of stainless steel production, activity of chromium oxide, aCrOy, and phase relations for the CaO-Si02-CrOy system have been investigated under moderately reducing conditions, Ib 2 =7.04 010-6 Pa at 1873 K. Activity coefficients of chromium oxides show strong dependencies on XCaOIXSi02, an index of basicity, and chromium content of the slag. Solubility of chromium oxide in the slag system drastically decreases with increasing XCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 5 publications
3
35
1
Order By: Relevance
“…21,23,24,42) With respect to g CrO , the basicity effect reported by these authors is consistent: they all found that g CrO increases with increasing slag basicity. This behavior is similar to that of other divalent transition metal oxides, such as FeO, MnO and NiO.…”
Section: Chromium Equilibriumsupporting
confidence: 67%
See 3 more Smart Citations
“…21,23,24,42) With respect to g CrO , the basicity effect reported by these authors is consistent: they all found that g CrO increases with increasing slag basicity. This behavior is similar to that of other divalent transition metal oxides, such as FeO, MnO and NiO.…”
Section: Chromium Equilibriumsupporting
confidence: 67%
“…For example, Pretorius and Muan 23) found that g CrO 1.5 decreases sharply in acid melts with increasing slag basicity and levels off at a mass% CaO/mass% SiO 2 ratio of around 0.7 in the CaO-SiO 2 -CrO x -Al 2 O 3 system at 1 783 K and at 10 Ϫ9.56 atmϽp O 2 Ͻ 10 Ϫ12.5 atm. On the other hand, for the CaO-SiO 2 -CrO x system at p O 2 ϭ6.95 · 10 Ϫ11 atm and at 1 873 K, Morita et al 21) observed a continuous increase of g CrO 1.5 in a C/S ratio (X CaO /X SiO 2 ) range between 0.6 and 1.5. Also Pei et al 24) investigated a CrOx in the CaO-SiO 2 -Al 2 O 3 -MgO sat.…”
Section: Chromium Equilibriummentioning
confidence: 97%
See 2 more Smart Citations
“…)-Gas system, using the thermodynamic properties of manganese and chromium in molten copper [9][10][11][12][13][14][15] summarized in Table 1(b), the standard Gibbs free energy change of the Reaction (2) in case of MϭCu, DG°2 ,MϭCu , and DG°f , MnO · Cr 2 O 3 were determined from the experimental results for this system. In case of this system, the dissolved chromium, oxygen and carbon in copper phase are so dilute that the terms of their interaction can be neglected.…”
Section: Standard Gibbs Free Energy Of Formation Of Mno-mentioning
confidence: 99%